ANALISIS PENGARUH SUMBER DAYA MANUSIA TERHADAP ASPEK KINERJA PEKERJA PADA PROYEK PEMBANGUNAN GEDUNG LABORATORIUM TERPADU PENDUKUNG BLOK MASELA UNIVERSITAS PATTIMURA - Siti Difinubun; Obednego Dominggus Nara; Maslan Abdin (Jurusan Teknik Sipil, 2023)
In this study which focuses on the four aspects studied, where for the main reason of being interested in aspects of human resources related to competence, motivation, loyalty and work discipline are general aspects that unwittingly exist in the worker himself and the worker is one of the triggers for the success of a construction project. These four aspects have an impact on the performance of workers, because the work does not reach the deadline. Thus, it gives rise to the desire to explore more deeply the reasons for work that does not reach the target and by increasing work time (overtime), because in the construction project of Masela Block Integrated Laboratory Supporting Buliding of Pattimura University has so many workers in their fields, it is felt that there is a slight delay due to the number of workers with the work itself. The study was conducted by distributing questionnaires for the distribution of questionnaires, the data analysis technique used was SPSS 26 software. Data analysis starts from validity test, reliability test, classical assumption test, namely normality test, descriptive analysis, multiple linear regression analysis and Relative Importance Index (RII) From the results of the analysis carried out on human resources on aspects of worker performance, multiple linear regression analysis shows that human resources have a positive and significant effect on worker performance, and the most dominant influence on the results of the RII calculation is the work discipline aspect, namely 0.820 or 82%, the second is the aspect, namely competency 0.411 or 41%, then the third aspect of motivational is 0.394 or 39% and the last is the loyalty aspect, namely 0.300 or 30%.